2017
DOI: 10.1017/s0959774317000816
|View full text |Cite
|
Sign up to set email alerts
|

Ideology, Ritual Performance and Its Manifestations in the Rock Art of Timor-Leste and Kisar Island, Island Southeast Asia

Abstract: Painted rock art occurs throughout the islands of the Western Pacific and has previously been argued to have motif and design elements in common, indicating that it was created within the context of a shared symbolic system. Here we report five new painted rock-art sites from Kisar Island in eastern Indonesia and investigate the commonalities between this art and the painted art corpus in Timor-Leste, the independent nation that forms the eastern part of the neighbouring island of Timor. We examine the motifs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 17 publications
(27 reference statements)
1
36
0
6
Order By: Relevance
“…The inhabitants of HSE could have moved to other locations on Kisar or neighbouring islands such as Timor, Wetar, Romang, or Leti in order to have access to more reliable water and food resources. The maintenance of the relationship between Kisar and Timor can be found in the rock art, oral history, language, and place names that are used together (O'Connor and Ono 2013;O'Connor et al 2018). Considering their developed seafaring culture (O'Connor, Ono, and Clarkson 2011) and indisputable evidence of the maritime transportation of obsidian between islands in the Lesser Sunda found by Reepmeyer et al (2016Reepmeyer et al ( , 2019, early and continuous cultural linkages between the two islands have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhabitants of HSE could have moved to other locations on Kisar or neighbouring islands such as Timor, Wetar, Romang, or Leti in order to have access to more reliable water and food resources. The maintenance of the relationship between Kisar and Timor can be found in the rock art, oral history, language, and place names that are used together (O'Connor and Ono 2013;O'Connor et al 2018). Considering their developed seafaring culture (O'Connor, Ono, and Clarkson 2011) and indisputable evidence of the maritime transportation of obsidian between islands in the Lesser Sunda found by Reepmeyer et al (2016Reepmeyer et al ( , 2019, early and continuous cultural linkages between the two islands have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the high archaeological potential on Kisar can be seen from the discovery of numerous caves and rockshelters containing rock art (O'Connor et al 2018) and also from the results of the small excavations conducted at here sorot entApA (hse) rocKshelter HSE consists of a rockshelter in a limestone terrace with a smaller cave chamber at the back (Figure 2). The shelter lies at a height of about 24 m above present mean sea level and is located approximately 80 m from the modern shoreline (O'Connor et al 2019).…”
Section: Kisar Islandmentioning
confidence: 97%
See 1 more Smart Citation
“…As noted, the last of these possibilities may be of most relevance to Gua Pondoa. Although it is possible that some of these scenes were painted in the Neolithic, O'Connor et al (2015O'Connor et al ( , 2018 have recently noted the similarity of some of the anthropomorphs shown in the Kisar and Timor Leste panels to scenes figured on Dong Son drums. Thus, the production of rock art may be referencing images seen on other types of material culture.…”
Section: Apt Cultural Foundations and Comparison With Other Sites In mentioning
confidence: 99%
“…A region with distinctive characteristics. Similarly, the islands' mound between Asia and Australia have a key role in explaining the complex process of human migration in the past (McKinnon, 1988;O'Connor et al, 2005;2018;Ririmasse, 2010: 71-89;2011: 23-38).…”
Section: Archaeology In Maluku: the Settingmentioning
confidence: 99%